2019
DOI: 10.15419/bmrat.v6i2.520
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 status in patients with primary breast cancer and its relationship with other prognostic factors

Abstract: Introduction: Breast cancer (BC) is the most common cancer in women and is the second most common cause of fatality in patients with cancer in the world. Cell proliferation plays an important role in the clinical behavior of invasive BC. We aimed to assess the status of Ki-67 in patients with primary breast cancer and evaluate the association of this tumor marker with other clinico-pathologic and prognostic factors. Methods: The current study recruited 220 patients with primary BC admitted to the oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
4
16
1
2
Order By: Relevance
“…Ki-67 levels showed no significant correlation with the patient's age, while they showed significant correlation with tumor size, node staging, the histopathological grade and NPI values. It was reported that the Ki-67 high levels show significant association with poor prognosis, short survival, and high mortality rate [14,15,16]. None of the previous studies, to the best of our knowledge, has revealed that Ki-67 is significantly correlated with patient's age, which is in concordance with this study [14,17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Ki-67 levels showed no significant correlation with the patient's age, while they showed significant correlation with tumor size, node staging, the histopathological grade and NPI values. It was reported that the Ki-67 high levels show significant association with poor prognosis, short survival, and high mortality rate [14,15,16]. None of the previous studies, to the best of our knowledge, has revealed that Ki-67 is significantly correlated with patient's age, which is in concordance with this study [14,17].…”
Section: Discussionsupporting
confidence: 90%
“…It was reported that the Ki-67 high levels show significant association with poor prognosis, short survival, and high mortality rate [14,15,16]. None of the previous studies, to the best of our knowledge, has revealed that Ki-67 is significantly correlated with patient's age, which is in concordance with this study [14,17]. Few studies concluded the Ki-67 significant correlation with tumor histopathological grade [18,19,20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, many studies demonstrated the reverse; with a positive correlation between Ki-67 and both 4 . Kremani et al found a marginal significant relationship between lymph node status and Ki-67 expression 8 .…”
Section: Discussionmentioning
confidence: 96%
“…La extensión de la enfermedad hacia los ganglios axilares sigue siendo el determinante más importante de sobrevida. En nuestro estudio no fue la excepción, encontrando relación directa y significativa con el Ki-67; así, mientras mayor número de ganglios axilares comprometidos se identificaron, mayor fue el porcentaje de expresión del Ki-67 (11) .…”
Section: Discussionunclassified